(3GdhOGFY GdeUQajI GdfbOjI hESJKeGQgG aj GdESdGe (B/s - (3YHOGddg GdCejf, MSfs ((3LOI(B: s (3OGQ GdTQhb(B, s, 1983)
(3GdhOjYI aj GdTQjYI GdESdGejI hehba GdbGfhf GdhVYj efgG hGdhOGFY GdeUQajI Ydi VhA GdbhGYO hCMcGe GdTQjYI efgG GdESJKeGQ aj GdhOGFY GdeUQajIs
Keywords: (3GdGSJKeGQs; (3GdGSdGes; (3GdHfhcs; (3GdeUGQas; (3GdhGOFYs